Prevalence of self-reported knee symptoms and management strategies among elderly individuals from Frederiksberg municipality: protocol for a prospective and pragmatic Danish cohort study. Issue 9 (4th September 2019) - Ginnerup-Nielsen, Elisabeth Marie; Henriksen, Marius; Christensen, Robin; Heitmann, Berit Lilienthal; Altman, Roy; March, Lyn; Woolf, Anthony; Karlsen, Hanne; Bliddal, Henning
Abstract : Introduction: The Global Burden of Disease 2010 study ranked osteoarthritis (OA) as a leading cause of years lived with disability. With an ageing population, increasing body weight and sedentary lifestyle, a substantial increase especially in knee OA (KOA) is expected. Management strategies for KOA include non-pharmacological, pharmacological and surgical interventions. Meanwhile, over-the-counter pain medications have been discredited as they are associated with several risks with long-term usage. By consequence, the use of exercise and all sorts of complementary and alternative medicine (CAM) for joint pain has increased. The available self-management strategies are plenty, but there is no overview of their use at a population level and whether they are used along with doctors' prescriptions or replace these. The aim of this study is to estimate the population incidence of developing knee symptoms and analyse the association between (and impact of) the use of self-reported preventive measures and knee symptoms. Methods and analysis: This prospective cohort study pragmatically recruits individuals from the municipality of Frederiksberg, Denmark. All citizens aged 60–69 years old will be contacted annually for 10 years and asked to participate in a web-based survey. The major outcomes are self-reported knee symptoms and their association with use of various management strategies, including use of non-pharmacological treatments and CAM. Secondary outcomes include the influence of treatments on use of healthcare system and surgical procedures. Descriptive and analytic statistics (eg, logistic regression) will be used to provide summaries about the sample and observations made and the associations between self-management and development of knee symptoms. Ethics and dissemination: This study can be implemented without permission from the Health Research Ethics Committee. Permission has been obtained from the Danish Data Protection Agency. Study findings will be disseminated in peer-reviewed journals and presented at relevant conferences. Trial registration number: NCT03472300 .